Diagnóza neplodnost : Sociologický pohled na zkušenost nedobrovolné bezdětnosti - Slepičková, Lenka (Masarykova univerzita, 2014)
The book examines infertility both as a medical condition and as a specific social status. The author identifies the relevance of infertility in life biographies in the context of Czech society which highly values parenting but has one of the lowest birth-rates in Europe. She is interested in how people are adapting to this situation of conflict between their life plans and physical and social barriers. The book contains four chapters of in-depth interviews and analyses. Each chapter deals with one particular dimension of experience with infertility and its treatment.